Analysis of Factors Affecting Economic Empowerment of Rural Women in Ethiopia: A Logistic Regression Model - Giziew, Almaz; Tesemma, Assaye (Journal of Agricultural Extension Management, 2018)
Without the participation of women in national activities, the social, economic or political progress of a country will be stagnated. However, women are hampered by socio-cultural norms, lack of resources and economic opportunities. Women’s economic empowerment helps to insure gender equality and the well being of nations. the purpose of the study was to study factors influencing economic empowerment of rural women in Bahir Dar Zuria district of Amhara region. The study was conducted using quantitative study design. The total sample size of the study was 120 respondents from four randomly selected kebeles of Bahir Dar Zuria District. The data collection was done through structured interview for quantitative survey and analyzed by using inferential statistics like chi-square test, v-test, Cramers's V, Pearson's Correlation Coefficient and regression model. Statistical Package for Social Sciences (SPSS) version 16.0 was used for data analysis. The study found that majority of rural women (75.83% ) were illiterate. The researchers found that majority of rural married women (42.4%) were economically dependent on their husbands and this economic dependency affected their decision making power, and made them submissive and subordinate. According to binary logistic regression model result: decision making on household matters, credit utilization and participation in non-farm activities affected women's economic dependency positively and significantly whereas age of the respondents affected rural women's economic independence negatively. Gender responsive programs should recognize that practices such as lack of access to and control over resources, and the absence of decision-making and negotiation power all negatively affect women's economic independence Special promotion and support have to be given to women during policy formulation and designing women sensitive issues and need based development.